Effect of sodium benzoate and chlorhexidine gluconate on a bio-thermoplastic elastomer made from thermoplastic starch-chitosan blended with epoxidized natural rubber - Araya Kodsangma (2020)
© 2020 Elsevier Ltd Thermoplastic elastomer (TPE) was developed by blending thermoplastic starch (TPS) with rubber. Thermoplastic starch-chitosan (TPSC) was prepared by the solution mixing of cassava starch, chitosan (CTS) and glycerol in acidified water (lactic acid 1 wt%) at 80 °C follow by melt mixing at 130 °C. Sodium benzoate (BEN) and chlorhexidine gluconate (Cl) were added during the solution mixing as additives for antimicrobial properties. TPSC was melt-mixed with epoxidized natural rubber (ENR) (70/30 wt/wt). The tensile strength and elongation at break of the TPSC/ENR increased with the additive content. Elastic recovery was improved by the addition of Cl. A new peak in the FTIR data confirmed the reaction between the reactive functional groups of the CTS and the additives with the epoxy groups of ENR. These reactions and miscibility of the TPSC/ENR/additives blends improved the mechanical properties, elasticity, morphology, and antimicrobial properties of the blends.